Perancangan Mesin Bubut Kayu Mini - Aditya , Jordy Lambang; Lutvi Arif Wibowo (Universitas Nusa Putra, 2021)
A mini wood lathe is a fairly simple machine, and one of the tools to shape various kinds of wood into a work of art is like making a chess piece. The most important parts are the electric motor, fixed head, loose head, retainers and propulsion unit, but until now there are still many wood industry entrepreneurs who still use makeshift tools so that the results are not optimal. Realizing these conditions, an effort is needed to create a mini wood lathe that is good and can be used to improve their production process. From the planning calculations carried out, and obtained a dimension of this mini wood lathe is 350mm high, 950mm long and 300mm wide which includes a cylindrical shaft with a diameter of 25mm which is also connected as a fixed head using a 13mm drill chuck, transmission pulley bearings, V-belt, 1.5 HP dynamo motor with a motor speed of 1500 rpm, with a workpiece capacity of 200mm diameter and 800mm length, and a frame as a holder for these components.